2D Nanoporous Fe−N/C Nanosheets as Highly Efficient Non‐Platinum Electrocatalysts for Oxygen Reduction Reaction in Zn‐Air Battery. Issue 41 (31st August 2016) - Yang, Zheng Kun; Lin, Ling; Xu, An‐Wu
Abstract : It is an ongoing challenge to fabricate nonprecious oxygen reduction reaction (ORR) catalysts that can be comparable to or exceed the efficiency of platinum. A highly active non‐platinum self‐supporting Fe−N/C catalyst has been developed through the pyrolysis of a new type of precursor of iron coordination complex, in which 1, 4‐bis(1H‐1, 3, 7, 8–tetraazacyclopenta(1)phenanthren‐2‐yl)benzene (btcpb) functions as a ligand complexing Fe(II) ions. The optimal catalyst pyrolyzed at 700 °C (Fe−N/C−700) shows the best ORR activity with a half‐wave potential (E1/2 ) of 840 mV versus reversible hydrogen electrode (RHE) in 0.1m KOH, which is more positive than that of commercial Pt/C (E1/2 : 835 mV vs RHE). Additionally, the Fe−N/C−700 catalyst also exhibits high ORR activity in 0.1m HClO4 with the onset potential and E1/2 comparable to those of the Pt/C catalyst. Notably, the Fe−N/C−700 catalyst displays superior durability (9.8 mV loss in 0.1m KOH and 23.6 mV loss in 0.1m HClO4 for E1/2 after 8000 cycles) and better tolerance to methanol than Pt/C. Furthermore, the Fe−N/C−700 catalyst can be used for fabricating the air electrode in Zn–air battery with a specific capacity of 727 mA hg −1 at 5 mA cm −2 and a negligible voltage loss after continuous operation for 110 h. Abstract : Self‐supporting Fe−N/C nanosheets are obtained from a new family of N‐rich Fe‐based coordination polymers, followed by pyrolysis. It shows excellent oxygen reduction activity under both acidic and alkaline conditions, better stability, and higher tolerance toward methanol crossover than Pt/C. When evaluated as the air cathode catalyst in Zn‐air battery, the Fe−N/C provides higher performance than that of Pt/C catalyst.